1992
DOI: 10.1177/000348949210101207
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies against a 30 Kilodalton Cochlear Protein and Type II and IX Collagens in the Serum of Patients with Inner Ear Diseases

Abstract: Collagen molecules are major extracellular matrix proteins involved in the development and support of delicate auditory sensory organs. Type II collagen is widely distributed within inner ear tissues, while type IX is found only within the labyrinthine membrane and dense fibers of the tectorial membrane. Antibody specific for type II collagen has been shown to be elevated in some patients with hearing loss due to several presumably autoimmune illnesses (including Meniere's disease, otosclerosis, chronic progre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
2
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(43 citation statements)
references
References 30 publications
2
38
2
1
Order By: Relevance
“…In a previous investigation we also found that 3 of 6 patients with Meniere's disease had antibodies directed against a 30-kD protein extracted from human inner ear in Western blotting [8]. Recently, using guinea pig innerear extracts, Cao et al [10] demonstrated that a 30-kD band was detected in sera from patients with various inner-ear diseases, especially in Meniere's disease and PSNHL, in accordance with our study.…”
Section: Introductionsupporting
confidence: 91%
“…In a previous investigation we also found that 3 of 6 patients with Meniere's disease had antibodies directed against a 30-kD protein extracted from human inner ear in Western blotting [8]. Recently, using guinea pig innerear extracts, Cao et al [10] demonstrated that a 30-kD band was detected in sera from patients with various inner-ear diseases, especially in Meniere's disease and PSNHL, in accordance with our study.…”
Section: Introductionsupporting
confidence: 91%
“…The different collagens might be particularly important for processes that sculpt the elaborate compartments of the inner ear during morphogenesis. This speculation is corroborated by the observation that perturbations of collagen metabolism lead to abnormal aural structure (31) and that autoimmune responses against type II and IX collagens culminate in progressive hearing loss (32,33). Candidate Genes for Hearing Disorders.…”
Section: Discussionmentioning
confidence: 89%
“…Clinical observations [32] and laboratory findings [33] as well as experimental evidence [34] are presented to support such an exciting hypothesis. However, the immunological theory comes up against the simple fact that the specificity of cochlear antigens against which antibodies have been described [35,36] is highly controversial. This makes it difficult to diagnose auto-immune disease when no systemic manifestations suggest an immune disorder.…”
Section: The Nosological Issuementioning
confidence: 99%